Influence of blood metabolites and body condition score at parturition on fertility and milk yield in Holstein cows - Torres, Edir; García, José E.; Véliz, Francisco G.; Leyva, Carlos; Macías-Cruz, Ulises; Hernández-Bustamante, Juan D.; Mellado, Miguel (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Variables associated with body tissue mobilization place dairy cows at greater risk of reproductive failure. Objective: To investigate the association between blood metabolites and body condition score (BCS) at the beginning of lactation and the reproductive efficiency and milk yield of Holstein cows in a hot environment. Methods: In total, 165 Holstein cows were selected for the study from which blood samples were taken to determine the concentration of various blood metabolites and their association with the reproductive efficiency and milk yield. Results: Cows with serum β-hydroxybutyrate (BHBA) ≤0.8 mmol/L one week postpartum were 3.3 times more likely to become pregnant at first service, and 2.2 times more likely to become pregnant before 80 d postpartum than cows with higher serum BHBA levels. The odds (OR 2.7; 95% CI 1.3–5.4; p<0.01) of a cow getting pregnant at first service were higher in cows with serum creatinine levels higher than 2.0 mg/dL one week postpartum than cows with lower blood levels of this metabolite. The BCS at 30 and 60 d postpartum that predicted pregnancy at first service and pregnancy to all services was 3.0. Blood urea nitrogen >15 mg/dL, creatinine <1.8 mg/dL, total protein ≤5.0 mg/dL one week postpartum, and >0.40 units of BCS loss during the first 30 d postpartum were critical threshold that predicted the likelihood of 305-d milk yield higher than 10,500 kg. Conclusions: Serum BHBA and creatinine one wk after calving as well as BCS 30 and 60 d post-calving provided reasonably accurate cut-off screening values to discriminate cows with better reproductive performance and higher 305-d milk yield.